2022
DOI: 10.7150/ijbs.71440
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Drives MiR-136-5p Expression to Promote Injury Repair after Myocardial Infarction

Abstract: Photobiomodulation (PBM) has emerged as an alternative therapy involved in modulating a variety of biological effects. In this study, we verified whether PBM can affect cardiac physiological activity in mice through noninvasive irradiation using light-emitting diodes at a wavelength of 630 nm (LED-Red). We found that the PBM involved in regulating the repair of injured myocardium is wavelength-limited. LED-Red caused cardiomyocytes (CMs) that had exited the cell cycle to divide and proliferate again, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Although previous studies have demonstrated the ability of PBM to prolong the growth cycle of outer root sheath cells and neural stem cells in vitro , the effect of LED-Red on CMs proliferation has not been elucidated yet 25 , 26 . In a previous study, we found that LED-Red with a power density of 2.5 mW/cm 2 irradiated for 10 min, could effectively elevating the viability of CMs without phototoxicity on CMs 27 . In addition to this, we determined the effect of LED-Red irradiation on the proliferation of neonatal CMs again.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Although previous studies have demonstrated the ability of PBM to prolong the growth cycle of outer root sheath cells and neural stem cells in vitro , the effect of LED-Red on CMs proliferation has not been elucidated yet 25 , 26 . In a previous study, we found that LED-Red with a power density of 2.5 mW/cm 2 irradiated for 10 min, could effectively elevating the viability of CMs without phototoxicity on CMs 27 . In addition to this, we determined the effect of LED-Red irradiation on the proliferation of neonatal CMs again.…”
Section: Resultsmentioning
confidence: 90%
“…LED-Red was identified to significantly increase the viability of CMs compared to blue, green and yellow light. Therefore, red light was chosen as the main light source for PBM 27 . MiRNAs have been reported to play a critical role in regulating key aspects of cardiac physiological and pathological signaling, including the regulation of cardiac regeneration in vitro and in vivo 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The other miRNAs listed in with higher fold change than miR-96-5p, such as miR-382-5p, miR-411-5p, miR-370-3p, and miR-31-5p, as well as their relationships with fibrosis in any other organ have never been studied. miR-199a-5p and miR-136-5p were shown to promote cardiac fibrosis [ 33 , 34 ] , while miR-455-3p was proven to inhibit the process of myocardial fibrosis [35] . Thus, the role of miR-96-5p in cardiac fibrosis was assessed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al [ 37 ] determined that LED-Red promoted cardiomyocyte (CM) division and proliferation, myocardial revascularization, and regeneration while reducing fibrosis area in MI mice, improving cardiac contractile function. MiR-136-5p was identified as a cardiac photo-sensitive miRNA with proliferation-promoting effects, and INO80 as a miR-136-5p binding target in CM proliferation regulation [ 37 ]. Grandinetti et al [ 38 ] showed that carvedilol and PBMT comparably ameliorated pulmonary congestion, left ventricle (LV) end-diastolic pressure, LV dilation, and LV systolic function.…”
Section: Reviewmentioning
confidence: 99%